FRI0485 Phenotype of anca associated vasculitis associates with major cardiovascular events: a retrospective observational study from the leeds vasculitis cohort. (12th June 2018) - Giollo, A.; Hensor, E.M.A.; Andrews, J.; Buch, M.H.
Abstract : Background: Patients with ANCA-associated vasculitides (AAV) are at increased risk of cardiovascular (CV) disease than the general population. The factors associated with CV involvement in AAV are poorly understood. Objectives: To explore whether patient and disease-related characteristics associate with CV disease from a single-centre AAV cohort. Methods: Medical records from 145 patients with AAV were reviewed and patients' diagnoses reclassified according to a validated algorithm. 1 CV events (CVE) were defined as myocardial infarction, cerebrovascular accident, thromboembolic event, heart failure, or death/hospitalisation due to CV cause. Time to first CVE was calculated; patients without CVE were censored at most recent clinical follow-up. Data on CV risk factors (hypertension, hyperlipidaemia, diabetes mellitus, chronic kidney disease stage III or higher) were collected. Putative predictors included age, sex, diagnosis (GPA, MPA, EGPA, unclassifiable AAV – UAAV), ANCA (absent, PR3, MPO), number of BVAS items, prior CV disease and number of CV risk factors. Cox proportional hazards regression was used to assess the relationship between CVE and predictors. In this exploratory analysis we used p<0.10 to indicate potential associations. Results: 122 patients who had been followed up for between 6 months and 23 years were included in the analysis. 11/122 patients (10%) had prior history of CV disease. 17 patients (14%) experienced a CVE within median (IQR) 5.8 (1.4, 7.6) years of diagnosis. Univariable analyses indicated older age at diagnosis, MPA and prior CVD were associated with increased risk of CVE, and that those with UAAV were at decreased risk compared to GPA. With the exception of previous CVD an adjusted model confirmed the same associations (table 1). Conclusions: This exploratory analysis suggests that, among AAV, MPA may have a higher CV risk, whereas UAAV may be associated with a decreased risk. Along with ANCA status, AAV phenotype may inform future CV risk reduction interventions in AAV. Reference: [1] Watts R, et al. Development and validation of a consensus methodology for the classification of the ANCA-associated vasculitides and polyarteritis nodosa for epidemiological studies. Annals of the Rheumatic Diseases2007. Disclosure of Interest: None declared